DETERMINATION of OPTIMUM CONDITION of PAPAIN ENZYME FROM PAPAYA VAR JAVA (Carica papaya) - Aline Puspita Kusumadjaja; Rita Puspa Dewi (Universitas Gadjah Mada, 2005)
A study to investigate the optimum condition of papain enzyme has been carried out. The condition that are investigated are pH and temperature, based on measurement of enzyme activity which is defined as mmole tyrosin that are released in reaction between papain enzyme and casein as substrat per minute. In this research, the papain enzyme was isolated from pepaya burung varietas Java. The enzyme was partially purified by precipitation method using 30% - 50% saturated acetone. The result showed that the optimum conditions of papain enzyme are in pH 6 with activity 2,606 U/mL, and temperature at 50 oC with activity 2,469 U/mL.